2011
DOI: 10.1103/physreva.83.032124
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of classical periodic orbits and quantum coherent states in coupled oscillators with SU(2) transformations

Abstract: The geometry of classical dynamics in coupled oscillators with SU(2) transformations is explored and found to be relevant to a family of continuous-transformation orbits between Lissajous and trochoidal curves. The quantum wave-packet coherent states are derived analytically to correspond exactly to the transformation geometry of classical dynamics. By using the quantum wave-packet coherent states derived herein, stationary coherent states are constructed and are shown to possess spatial patterns identical to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 46 publications
(64 reference statements)
0
30
0
Order By: Relevance
“…We would like to remark that, in view of the case (p,q) = (1 , 1) for the coupled isotropic HO, the wave functions have been demonstrated previously on a group theory level via the SU(2) transformation [28,31]. Likewise, it enables us to derive the wave functions by employing the transformation of the SU(2) symmetry group.…”
Section: Theoretical Modelmentioning
confidence: 67%
See 2 more Smart Citations
“…We would like to remark that, in view of the case (p,q) = (1 , 1) for the coupled isotropic HO, the wave functions have been demonstrated previously on a group theory level via the SU(2) transformation [28,31]. Likewise, it enables us to derive the wave functions by employing the transformation of the SU(2) symmetry group.…”
Section: Theoretical Modelmentioning
confidence: 67%
“…(1). The coupling termĤ c is introduced as an SU(2) coupling interaction [27,28], which can be modeled aŝ…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In common non-degenerate states, it has been confirmed that the high-order HG mode can be experimentally generated under off-axis pumping with a sufficiently large off-axis displacement [35,38]. Whereas in degenerate states, it has been theoretically and experimentally confirmed that the emission mode can be characterized by the quantum coherent states with SU(2) Lie algebra [33]: where M + 1 stands for the number of HG modes in family of ψ (HG) n 0 +Q·K,0,s 0 −P ·K (x, y, z) with K = 1, 2, 3, · · · , which constitute a family of frequency-degenerate modes, where n 0 and s 0 represent the minimum transverse and maximum longitudinal orders in the degenerate family respectively. Note that all the discussion corresponding to the off-axis pumping with (∆x, 0) can be applied to the case of (0, ∆y) for the degenerate family in terms of ψ (HG) 0,m 0 +Q·K,s 0 −P ·K (x, y, z).…”
Section: A Frequency-degenerate Resonatormentioning
confidence: 91%
“…Complex poles corresponding to the unstable oscillator then arise in the complex energy plane. From another point of view, the a i 's can be regarded as the normal modes of two degenerate oscillators coupled through the SU(2) coupling interactions [19]. The system Hamiltonian H is then unitarily related to a family of Hamiltonians by SU (2) transformation.…”
Section: The Hamiltonianmentioning
confidence: 99%